The Interaction of Elderly Individuals in Learning to Read the Qur'an - Nuzula, Firdausi; Mahmud, Amir; Rohtih, Wiwin Ainis (Study Program of Arabic Language Teaching, 2025)
This study aims to examine the interaction of elderly individuals in learning to read the Qur’an, particularly in the context of the implementation of Surah Al-Qamar, verse 17. It also analyzes the teaching strategies employed, the symbolic interaction between participants and the Qur’an, and the learning motivation among elderly learners. This research was conducted at Pondok Pesantren Hidayatul Hidayah, located in Dusun Mojogeneng, Desa Mojogeneng, Kecamatan Jatirejo, Kabupaten Mojokerto, East Java. The pesantren provides Qur’anic learning programs for elderly learners in a supportive and age-friendly environment. This study adopts a qualitative approach utilizing a case study method with data obtained through in-depth interviews, observation, and documentation. The collected data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing to interpret the interaction of elderly learners in Qur’anic education. The findings reveal that applying the values contained in Surah Al-Qamar:17 strengthens participants’ faith and perseverance in learning the Qur’an. Meanwhile, adaptive teaching strategies that align with the characteristics of older adults play a crucial role in maintaining their motivation. The symbolic interaction developed between the participants and the Qur’an provides profound spiritual and emotional meaning, serving as a key driver for the continuity of learning in old age. The study also reveals that the motivation of elderly learners is not solely intrinsic but is also influenced by social support from their surrounding environment. However, the study's limitation lies in its focus on a single research site and its reliance on subjectively interpreted qualitative data, which should be considered when generalizing the findings. These results are expected to serve as a foundation for developing more effective and compassionate methods of Qur’anic instruction for elderly learners.